Multidisciplinary Approaches to Allergies - Gao, Zhong-Shan.; Zheng, Min.; Gilissen, Luud J. W. J.; Shen, Hua-Hao.; Frewer, Lynn J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Allergy is an immunological disease caused by multiple factors and characterized by variability, specificity and complexity. "Multidisciplinary Approaches to Allergies" covers diverse aspects ranging from basic molecular mechanisms to societal issues within the framework of multidisciplinary approaches to allergies. It contains 29 chapters in 6 parts: General Allergy; Allergenic Sources and Allergens; Diagnosis; Therapies and Pharmacy; Hypoallergenic Products; Environment, Hygiene and Societal Issues. It can be used in education and research as introductory and supplementary material. It is also an indispensable tool for scientists and doctors who are searching for an integrated way for allergy prevention, treatment and management. Zhong-Shan Gao, Ph.D., is Professor of Fruit Science and Allergy at the Department of Horticulture and the Allergy Research Center, Zhejiang University, China. Hua-Hao Shen, M.D., Ph.D., is Professor of Respiratory Diseases at the Second Affiliated Hospital, School of Medicine, Zhejiang University, China, and Professor in the Chang Jiang Scholars Program (MOE). Min Zheng, M.D., Ph.D., is Professor of Dermatology at the Second Affiliated Hospital, School of Medicine, Zhejiang University, China. Lynn J. Frewer, Ph.D., is Professor of Food & Society at the School of Agriculture, Food and Rural Development, Newcastle University, UK. Luud J.W.J. Gilissen, Ph.D., is senior researcher at Plant Research International, Wageningen University and Research Centre, the Netherlands.
Allergenic Sources and Allergens -- Diagnosis -- Therapies and Pharmacy -- Hypoallergenic Products -- Environment, Hygiene and Societal Issues.
Keywords: Life sciences; Biotechnology; Food science; Pharmacy; Allergy; Environmental Medicine; Life Sciences; Life Sciences, general; Allergology; Biotechnology; Food Science; Environmental Health; Pharmacy